The Influence of Project Manager Competency and Construction Worker Competence toward Performance of Construction Workers Medicated Variables of the Application of Occupational Health and Safety (OHS) Management System - Ardi Syah, Didi (International Journal of Management and Education in Human Development, 2021)
Performance in the field of infrastructure, especially construction has a high risk as a result many work accidents are found so there needs to be a competency application (manager and worker) in the project to avoid work accidents and achieve the quality of construction performance. The purpose of this study was to analyze the influence between the potential of construction managers and the potential of construction workers on the success of construction work performance by implementing the Occupational Safety and Health Management System (SMK3) as a mediating variable. The object of this research is the construction work of the Bahteramas-Kendari Bay bridge construction in Kendari City, Southeast Sulawesi Province, Indonesia. This study uses a quantitative approach. Respondents were 100 people, 85 construction workers and 15 manager-level people. The sample is determined by random sampling stratification technique. Data were analyzed using smart PLS. The analysis shows that the competence of construction managers (X1) has a positive and significant effect on the occupational safety and health management system (Z) where the t-statistic value of 27.723 is greater than 5.4129 (t-table). Construction manager competency (X1) has a positive and significant effect on the success of construction worker performance (Y) where the t-statistic value of 5.8998 is greater than 1.965 (t-table). Construction worker competency (X2) has a positive and significant effect on occupational safety and health management systems (Z) where the t-statistic value of 10.4948 is greater than 1.965 (t-table). Construction workers competency (X2) has a positive and significant effect on the success of construction workers performance (Y) with a t-statistic value of 4.0056 greater than 1.965 (t-table). Occupational health and safety management system (Z) has a positive and significant effect on the success of construction worker performance (Y) where the t-statistic value of 2.0909 is greater than 1.965 (t-table). Occupational safety and health management system (Z) as a mediator between construction manager competencies (X1) to the success of construction workers performance (Y) is significantly positive where the t-statistic value of 2.52 is greater than t-table 1.965, and mediates the competence of construction workers (X2) on the success of construction workers performance (Y) is significantly positive with a t-statistic value of 4.858.